(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize major bioactive compound groups and preclinical evidence on medical application–related effects of seahorses (Hippocampus spp.). Methods: A structured narrative review was conducted by searching PubMed, Web of Science, Scopus, Google Scholar, and CNKI up to 30/11/2025. Results: Seahorses are rich in proteins/amino acids and contain peptides, glycoproteins, sterols, unsaturated fatty acids, and trace elements. In vitro and in vivo studies indicate antioxidant activity; improved endurance indices and post-exertion fatigue-related markers; improved sperm parameters and testosterone in rat models of reproductive impairment; and limited signals for anti-inflammatory/immunomodulatory effects, neuroprotection, and UV-related anti-photoaging effects. Safety data remain limited, with concerns regarding quality variability and environmental contaminants; moreover, many species are listed in CITES Appendix II, underscoring the need for legal supply chains and sustainable aquaculture. Conclusion: No human clinical trials were identified; therefore, current evidence is insufficient to recommend therapeutic use. Future work should prioritize product standardization, toxicity–interaction assessment, and well-designed controlled clinical trials.